1987
DOI: 10.1002/bem.2250080208
|View full text |Cite
|
Sign up to set email alerts
|

Acute exposure of rats to air ions: Effects on the regional concentration and utilization of serotonin in brain

Abstract: Exposure to electrically charged gas molecules (air ions) has been reported to influence physiological and behavioral functions in animals and humans although there is controversy as to whether these findings are valid. A popular hypothesis concerning the reported effects of air ions is that alterations in serotonin (5HT) metabolism, particularly in the brain, are involved. We measured the concentration and turnover of 5HT in rats exposed to 5.0 X 10(5) ions/cm3 for up to 66 hours. Contrary to previous reports… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…Another study reported an elevation of brain serotonin after positive ion exposure with a decrease following negative ion exposure, using 700,000 ions/cm3 in both cases (Beardwood et al, 1987). Three recent studies, however, using exposures of 500,000 to 1.5 million ions/cm3 for similar periods showed no effect on serotonin or serotonin precursors and metabolites (Dowdall and de Montigny, 1985;and Bailey and Charry, 1987). In addition, Charry and Bailey (1 985) failed to find any effect of air ion exposures on the concentration and utilization of norepinephrine and dopamine -two other neurotransmitters in brain (Charry and Bailey, 1985).…”
Section: Serotonin Metabolismmentioning
confidence: 95%
“…Another study reported an elevation of brain serotonin after positive ion exposure with a decrease following negative ion exposure, using 700,000 ions/cm3 in both cases (Beardwood et al, 1987). Three recent studies, however, using exposures of 500,000 to 1.5 million ions/cm3 for similar periods showed no effect on serotonin or serotonin precursors and metabolites (Dowdall and de Montigny, 1985;and Bailey and Charry, 1987). In addition, Charry and Bailey (1 985) failed to find any effect of air ion exposures on the concentration and utilization of norepinephrine and dopamine -two other neurotransmitters in brain (Charry and Bailey, 1985).…”
Section: Serotonin Metabolismmentioning
confidence: 95%
“…This was the only study that was explicitly conducted under blinded conditions. Seven studies focused on the effects of air ions [3843, 73]; these studies were included in this review because they also tested a static EF alone. An additional four studies investigated exposures to EF from a HVDC line [44, 45] or a simulated HVDC environment [46, 47].…”
Section: Resultsmentioning
confidence: 99%
“…Given that longer or repeated exposures to negative air ions were not observed to strengthen the response of subjects, additional investigation of the biological plausibility is warranted. The concentrations of air ions expressed as parts per trillion are vanishingly small and well-controlled animal studies do not report changes in catecholamine neurotransmitter levels [50] or the levels and turnover of serotonin in the brain [49] even though opposing effects of longer-term exposure to negative and positive air ions on the responsiveness of hippocampal neurons to serotonin have been reported [51].…”
Section: Discussionmentioning
confidence: 99%
“…Presumably, the greater the ion concentration, combined with longer exposure durations at greater frequency, the greater the likelihood for air ion exposure to produce a biological response in exposed subjects, if in fact a real association is present. While there is no consistent support in animal studies for effects of negative or positive air ion treatment on central nervous system neurotransmitter systems linked to depression [21,49,50], Dowdall and De Montigny [51] have reported that continuous exposure of rats to negative air ions at a density of 1.5 × 10 6 ions/cm 3 for 21 days increases the response of hippocampal pyramidal neurons to iontophoretically applied serotonin as do several antidepressant drugs. Nonetheless, human studies to date on the relationship between exposure duration, within high and low air ion concentrations, and depression symptom severity do not support such a relationship.…”
Section: Discussionmentioning
confidence: 99%